Analisis Resiko Bisnis - Fitri Hotdiana H.; Ary Ahmad Yani; Mulyani Putri; Suhairi Suhairi (LPPM IAI Nasional Laa Roiba Bogor, 2022)
Perfect understanding of risk, can turn risk into opportunity. no exception in the global business / business, conditions filled with uncertainty can affect the success of a business. Strategic and tactical decisions designed by management that initially aim to realize the company's vision and mission, if they do not take into account the risks that may exist, may result in these decisions resulting in the achievement of the company's vision and mission not being achieved. Risk management is better known as Risk Management. there are three crucial terms in risk management, namely identification, measurement and risk mapping. 3 risk criteria that are likely to be faced by the company, namely Financial Risk, Operational Risk, and Externalization Risk. Risk management is the design of mechanisms and implementation of procedures to manage a business risk. Where not infrequently the decisions taken are not looking at the magnitude of the risk that will occur but rather looking at the amount of profit that will be received. This is because humans have an ambitious nature to achieve high profits and want to quickly leave the difficult period, including financial difficulties. The current era is the era of consumerism.This research is a research that aims to determine the business risks and their functions applied to the company, knowing the stages of risk management and how to anticipate business risks that occur in the company. Business risk means the company's vulnerability to factors that can reduce its benefits or cause the company to fail. By implementing risk management in the company, it will provide great benefits for the company in managing its company. Several stages in carrying out risk management are: identification of risk, identifying forms of risk, placing risk measures, placing alternatives, analyzing every other way, determining one other way, implementing the chosen alternative, controlling the chosen alternative, evaluating the chosen alternative path. Keywords: Business Risk Management, Financial Risk